IoT-Based Air Quality Monitoring and Analysis at MSME Locations - Fitria, Fitria; Pebriadi, Muhammad Syahid; Windarsyah, Windarsyah; Rakhmawati, Aneta; Khalid, Anhar (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
Air is a crucial element that affects the survival of living things, but air pollution is often overlooked, especially in areas with intensive human activities, such as MSME locations. This research aims to design an Internet of Things (IoT)-based air quality monitoring device in MSME trader locations, especially in open spaces exposed to cigarette smoke and closed air-conditioned spaces. The method used was a quantitative descriptive approach with experiments, collecting primary data through an MQ-135 air quality sensor that measured the concentration of gases such as CO and NH3. The results showed that in an air-conditioned room, the gas concentration was detected at 536.00 PPM, while in the cigarette smoke area it was 197.36 PPM. A significant decrease in sensor resistance at both locations indicates the presence of air pollution that is harmful to health. Data were collected continuously for seven days. Based on OSHA exposure limits, concentrations above 50 ppm may pose health risks, indicating that the detected 536 ppm is significantly beyond safe thresholds. This device demonstrates real-time environmental monitoring applicability for MSME settings. This study proposes continuous monitoring and pollution mitigation to improve air quality and reduce health impacts.